Anatomical spread of local anesthetic in circumpsoas block: a cadaveric study - Atalay, Yunus Oktay; Sözcü, Semih Burak; Tekin, Bahar; Ansen, Gamze; Cingöz, Gözde; Şakul, Bayram Ufuk; Alıcı, Haci Ahmet (My University, 2025)
...
Keywords: Opiate; Local Anesthetic Agent; Letter